2016
DOI: 10.1186/s12986-016-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-mangostin from mangosteen (Garcinia mangostana Linn.) pericarp extract reduces high fat-diet induced hepatic steatosis in rats by regulating mitochondria function and apoptosis

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is caused by multiple factors including hepatic oxidative stress, lipotoxicity, and mitochondrial dysfunction. Obesity is among the risk factors for NAFLD alongside type 2 diabetes mellitus and hyperlipidemia. α- mangostin (α-MG) extracts from the pericarps of mangosteen (Garcinia mangostana Linn.) may regulate high fat diet-induced hepatic steatosis; however the underlying mechanisms remain unknown. The aim of this study was to investigate the regulatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 26 publications
2
55
0
3
Order By: Relevance
“…We speculated that a decrease in MDA was due to the scavenging of free radicals by MPP compounds, and to promoting activities of antioxidant enzymes in prostate tissues. In a previous study, mangosteen pericarp extract supplementation for 11 weeks produced significantly decreased plasma MDA levels and increased activities of superoxide dismutase (SOD), GPx, GRd, and CAT in rats fed an HFD 37 . Fang et al 38 demonstrated that α-mangostin treatment resulted in increases in SOD and GPx activities and the GSH content of the retina both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…We speculated that a decrease in MDA was due to the scavenging of free radicals by MPP compounds, and to promoting activities of antioxidant enzymes in prostate tissues. In a previous study, mangosteen pericarp extract supplementation for 11 weeks produced significantly decreased plasma MDA levels and increased activities of superoxide dismutase (SOD), GPx, GRd, and CAT in rats fed an HFD 37 . Fang et al 38 demonstrated that α-mangostin treatment resulted in increases in SOD and GPx activities and the GSH content of the retina both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…Taher and his group found that administration of ethanolic extract of G. mangostana pericarp to normoglycaemic and STZ‐induced diabetic rats significantly ameliorated blood glucose level, lipid profile, plasma lipid and kidney function parameters, and hepatic histological alterations; possibly via increasing the number of insulin‐producing β‐cells (Taher et al., ). Tsai and team observed that α‐mangostin (from mangosteen pericarp) treatment for 11 weeks significantly reduced HFD‐induced hepatopathy through enhancing cellular antioxidant capacity, improving mitochondrial functions, and suppressing hepatocytes apoptosis (Tsai et al., ). It suggests that α‐mangostin contained MVR, which may reduce the renal apoptosis through improving mitochondrial integrity and diminishing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…M. indica ở nồng độ IC10 đã kích thích tạo gốc iROS sau khi xử lý thêm với TBH và làm tăng lượng iROS khoảng 20%, trong khi G. mangostana và T. catappa lại làm giảm iROS (số liệu không trình bày). Phát hiện này cũng được thông báo trong một số nghiên cứu trước đây (Tsai et al, 2016;Moongkarndi et al, 2004;Huang et al, 2018). Sự ức chế iROS của G.mangostana và T. catappa khác biệt đáng kể ở nồng độ sử dụng IC25 và IC50.…”
Section: Khả Năng Triệt Tiêu Gốc Tự Do Hydroxyl/peroxylunclassified